Development of instrument to measure impression management among flood victims - Mustaffa, Che Su; Marzuki, Najib Ahmad; Khalid, Mohamad Sukeri; Ariffin, Mohd Taib; Mohd Salleh, Nurul Aina; Zakaria, Nurlela; Shafai, Syazwani; Shuhaimi, Amarul Waqi (American Scientific Publishers, 2015)
The purpose of this paper is to discuss about the development of an instrument to measure impression management.Impression management involves attempts to establish the meaning or purpose of social interactions, guides actions and helps us anticipate what to expect from others.Although interest in the area of impression management continues to grow, the lack of a measure that is both grounded in theory and well-suited for organizational use has slowed the progress in this area. The paper is based on a quantitative approach. The data were collected through a survey among 759 respondents.It offers to understand characteristics of impression management in the areas of disaster management in Malaysian organizations.We found four stable dimensions which measure impression management among flood victim in Malaysian contexts.Moreover, scores on the scale developed to measure the impression management criteria yielded excellent validity and reliability estimates.This study provided and presented insights and further understanding of impression management from the indigenous perspective, which allows practitioners to gain in-depth knowledge about the implementation of impression management in an organization.The implications of this research were discussed.